RISK MANAGAMENT IN LOGISTICS NETWORKS: AN OVERVIEW OF THE FIELD AND SOME NOVEL PERSPECTIVES - Skapinyecz, Róbert; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2018)
The publication covers a topic that is gaining more and more significance, namely the area of risk management in logistics networks. This domain became a focus of attention lately for a number of reasons, but most importantly because of the increasing sensitivity of global supply chains to various disturbing effects. Another important reason is the trend of digitalization, which naturally increases the significance of information-based collaboration inside the logistics networks, but it also raises more questions regarding the reliability of the participating elements. Taking into account the previous considerations, the publication tries to provide a comprehensive picture about the current status of the field. Based on the survey of the related literature, it introduces the background and the significance of the topic while also presents the most important trends, the frequently used approaches and a number of related examples. Moreover, partly based upon the conclusions drawn from the literature review, a novel approach for solving the problem is also proposed that could be successfully utilized in the future.